Analisis Karakteristik Serat Pandan Bali dan Sabut Kelapa dengan Perlakuan NaOH sebagai Penguat Polyester Komposit: Analysis of Bali Pandan Fiber and Coconut Fiber Characteristics with NaOH Treatment as a Polyester Composite Reinforcer - Ida Ayu Putu Indah Komala Dewi; IK Suarsana; IGP Agus Suryawan; Kadek Rihendra Dantes; I Putu Lokantara; I Made Astika; I G N Nitya Santhiarsa (Universitas Pendidikan Ganesha, 2025)
The development of composite materials has become a major focus of research in recent decades, especially natural fiber composites with a unique combination of physical and mechanical properties of materials. Polyester composites can be produced by utilizing synthetic and natural fibers. The natural fibers studied are the characteristics of Balinese pandan fiber and coconut fiber with NaOH solution treatment for polyester composite reinforcement. The treatment of Balinese pandan fiber and coconut fiber was carried out by soaking in a 10% NaOH solution, aiming to remove lactic acid and cellulose, in order to increase the bond between the polyester matrix and the fiber, both Balinese pandan fiber and coconut fiber. In this study, the effect of soaking time of Balinese pandan fiber and coconut fiber on the characteristics of physical properties was studied through Thermogravimetric Analysis (TGA) testing, with LECO USA machine specifications, model: 604-100-700, series: 6204 at the UNUD Mechanical Engineering Laboratory. This test was carried out by soaking Balinese pandan fiber and coconut fiber in a 10% NaOH solution at various soaking times: 1 hour, 2 hours and 3 hours. Then the Thermogravimetric Analysis (TGA) test was carried out, then the characteristics and physical properties of the Balinese pandan fiber and coconut fiber were obtained in the form of dust content, water content, volatile, fix Carbon. Based on the test results data on the 10% NaOH treatment, for coconut fiber soaked for 2 hours, the highest Fix Carbon level was obtained, namely 21.15 and the highest Balinese pandan fiber was 15.50, which can be used for bending test materials. In Balinese pandan fiber, the highest volatile level was obtained at 89.81 and coconut fiber 80.73, which can be used for sound absorption test materials.